2017
DOI: 10.4067/s0718-95162017005000020
|View full text |Cite
|
Sign up to set email alerts
|

Can biochar provide ammonium and nitrate to poor soils?: Soil column incubation

Abstract: Understanding how nitrogen concentrations respond to biochar amendment in different types of soils is important for agricultural management. Here, we analyzed the effects of amendment with rice hull biochar on sandy soil, red soil, and alkaline soil (coastal solonchak) over 13 months, focusing on factors such as ammonium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
3
9
0
1
Order By: Relevance
“…Herein, increases in AEN and REN in rice and wheat were recorded with the application of RSB and N (Table 7), which can be ascribed to increases in soil N supply and reduction in N losses. Earlier studies by Cao et al (2017) and Yao et al (2012) showed that incorporation of biochar in a sandy soil increased retention of ammonium and nitrate, thereby reducing N loss by leaching and reducing N 2 O emissions (Wu et al, 2013). Accordingly, Zhang et al (2015) reported that combined application of biochar and N fertilizer increased the AEN and REN in rice over no biochar.…”
Section: Crop Yield and N Use Efficiency As Affected By Biocharmentioning
confidence: 97%
“…Herein, increases in AEN and REN in rice and wheat were recorded with the application of RSB and N (Table 7), which can be ascribed to increases in soil N supply and reduction in N losses. Earlier studies by Cao et al (2017) and Yao et al (2012) showed that incorporation of biochar in a sandy soil increased retention of ammonium and nitrate, thereby reducing N loss by leaching and reducing N 2 O emissions (Wu et al, 2013). Accordingly, Zhang et al (2015) reported that combined application of biochar and N fertilizer increased the AEN and REN in rice over no biochar.…”
Section: Crop Yield and N Use Efficiency As Affected By Biocharmentioning
confidence: 97%
“…2), and its high CEC (Table 3) may contribute to the increase of soil CEC (Naeem et al 2017). Generally, biochar is a porous material with a high surface area and thus has a high sorption capacity, which may enhance soil CEC (Laird et al 2010;Cao et al 2017). In addition, mineralization of biochar can increase the CEC of the soil by releasing charged low-molecular weight humiclike substances (Mete et al 2015).…”
Section: Soil Ph and Cecmentioning
confidence: 99%
“…Hence, the biochar can be used as a substitute for phosphate fertilizers when reclaiming calcareous sandy soils because of its high content of P (0.6 to 3.2 g kg -1 ) that amount depends on the type of plant residues (Shenbagavalli and Mahimairaja, 2012). The incorporation of biochar with sandy soils results an increase in ammonium and nitrate retention and a reduction of nitrogen loss by leaching (Yao et al, 2012;Cao et al, 2017), and N 2 O emissions (Wu et al, 2013). So, it enhances the nitrogen use efficiency of plants grown in a sandy soil (Van Zwieten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%